Sazonalidade na qualidade do leite cru refrigerado - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
Milk production in the state of Goiás is highly heterogeneous, with biological, physiological, and environmental factors affecting its physicochemical composition. The objective of this study was to evaluate the effects of seasonality on the quality of refrigerated raw milk in western Goiás. Located in the Central-West region of Brazil, milk production is one of the fastest-growing agricultural sectors in the state, boasting favorable characteristics for milk production and a climate suitable for raising various breeds of dairy cattle. However, seasonality in the climate impacts pasture quality according to the seasons (spring, summer, fall, and winter), with long dry periods and rainy periods. This impacts the quality of the herd's feed, resulting in changes in the physicochemical parameters of the milk, resulting in loss of quality. Physical and chemical parameters, composition, and hygiene and health indicators change as a result of climate change throughout the year. High and low temperatures affect the welfare of dairy cattle. Dairy companies are increasingly demanding when purchasing refrigerated raw milk; fresh milk must meet the criteria established by the Ministry of Agriculture, Livestock, and Supply (MAPA). In accordance with the minimum established standards of: fat, density, titratable acidity, cryoscopic index, protein, total dry extract (TDI), defatted dry extract (DDI), lactose, alizarol and free of additions of acidity neutralizers, preservatives and density reconstitutes, standard plate count (SPC) and somatic cell count (SCC), in accordance with normative instruction no. 76 of 2018. The milk procurement market is increasingly demanding regarding quality and compliance with legislation, which highlights the need for rigorous quality control at all stages of production, from handling to storage and transportation of milk.
Seasonality in the quality of refrigerated raw milk
Keywords: Ambiente; Bovinocultura de leite; Condições higiênicas; Época do ano; Produção animal; Environment; Dairy farming; Hygienic conditions; Time of year; Animal production; CIENCIAS AGRARIAS